The in vivo dsRNA Cleavage Has Sequence Preference in Insects - Guan, Ruobing; Hu, Shaoru; Li, Haichao; Shi, Zhenying; Miao, Xuexia (Frontiers in Physiology, 2018)
The exogenous dsRNA enters the insect body can induce the RNAi effect only when it is cleaved into siRNA. However, what kinds of base composition are easier to be cut and what kinds of siRNA will produce in vivo is largely unknown. In this study, we found that dsRNA processing into siRNA has sequence preference and regularity in insects. We injected 0.04 mg/g dsRNA into Asian corn borer or cotton bollworm according to their body weight, and then the siRNAs produced in vivo were analyzed by RNA-seq. We discovered that large amount of siRNAs were produced with GGU nucleotide residues at the 5’- and 3’-ends, and produced a siRNA peak on the sequence. Once the GGU site is mutanted, the siRNAs number will decrease significantly, and the siRNA peak will also lost. However, in the red flour beetle, a member of Coleoptera, dsRNA was cut at more diverse sites such as AAG, GUG, and GUU, more importantly, these enzyme restriction sites have a high conservation base of A/U. Our discovery about dsRNA in vivo cleavage preference and regularity will help us understand the RNAi mechanism and its application.